Loss of Function in Dopamine D3 Receptor Attenuates Left Ventricular Cardiac Fibroblast Migration and Proliferation in vitro - Kisling, Andrew; Byrne, Shannon; Parekh, Rohan U.; Melit-Thomas, Deepthy; de Castro Brás, Lisandra E.; Lust, Robert M.; Clemens, Stefan; Sriramula, Srinivas; Katwa, Laxmansa C. (Frontiers in Cardiovascular Medicine, 2021)
Evidence suggests the existence of an intracardiac dopaminergic system that plays a pivotal role in regulating cardiac function and fibrosis through G-protein coupled receptors, particularly mediated by dopamine receptor 3 (D3R). However, the expression of dopamine receptors in cardiac tissue and their role in cardiac fibroblast function is unclear. In this brief report, first we determined expression of D1R and D3R both in LV tissue and fibroblasts. Then, we explored the role of D3R in the proliferation and migration of fibroblast cell cultures using both genetic and pharmaceutical approaches; specifically, we compared cardiac fibroblasts isolated from left ventricles (LV) of wild type (WT) and D3R knockout (D3KO) mice in response to D3R-specific pharmacological agents. Finally, we determined if loss of D3R function could significantly alter LV fibroblast expression of collagen types I (Col1a1) and III (Col3a1). Cardiac fibroblast proliferation was attenuated in D3KO cells, mimicking the behavior of WT cardiac fibroblasts treated with D3R antagonist. In response to scratch injury, WT cardiac fibroblasts treated with the D3R agonist, pramipexole, displayed enhanced migration compared to control WT and D3KO cells. Loss of function in D3R resulted in attenuation of both proliferation and migration in response to scratch injury, and significantly increased the expression of Col3a1 in LV fibroblasts. These findings suggest that D3R may mediate cardiac fibroblast function during the wound healing response. To our knowledge this is the first report of D3R’s expression and functional significance directly in mouse cardiac fibroblasts.